Study of efficiency of crude extract of local Horsetail Equiaetum arvense L. in blood coagulation (Baghdad Science Journal, 2025)
This study has been performed on the vegetative parts of the local Horsetail Equisetum arvense L.,which grow naturally in Haj Umran , north of Iraq , included some heamatological tests coccerning blood coagulation by using different concentration of both water and ethanolic extracts in vitro and in vivo . The results revealed that water extract of (25 and 50) mg/ml decreased clotting time in vitro, but higher concentration (100) mg/ml had reverse effect ( stoped coagulation) , Also the low concentration of crude extracts (water and ethanolic) were very efficient to decrease clotting time, and increase platelet count in vivo. But higher concentration (100) mg/ml increased the clotting time with decrease in platelet count .